Ce n’est pas toi, c’est la structure: déconstruction de la polyamorie féministe. Coral Herrera Gómez - Herrera Gómez, Coral; Coladan, Elisende (Non monogamie féministe, 2016)
La polyamorie féministe est une nouvelle utopie collective pour celles qui rêvent d’un monde égalitaire, féministe et multiple. Dans ce monde idéal, nous, les femmes, nous ne serions pas divisées e…
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; cours; espagne; europe; fem1000; pratiques féministes; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; sexualité; thématiques

Gay and lesbian literature disrupting the heteronormative space of the high school english classroom - Helmer, Kirsten (Sex Education: Sexuality, Society and Learning, 2016)
This paper offers insights into how the teaching of queer topics in English language arts classes can be reframed by bridging the goals, practices and conceptual tools of queer theory to literacy teaching. Drawing on an ethnographic classroom study, which explored a 13-week high school Gay and Lesbian Literature course, this paper discusses how teaching an English literature curriculum centred on the voices and stories of LGBTQI people constitutes a meaningful site for learning and teaching. In the process, I show how a queer-themed literature curriculum not only intervenes disruptively into the heteronormative space of school through its content but also through pedagogical practices that open up new lines of thinking for understanding diverse sexualities and genders. Through vignettes from the classroom, I illustrate how queer moments were enacted in this high school course as the class (a) deconstructed literary and media texts; (b) used moments of discomfort for learning; (c) produced counter-narratives through creative acts; and (d) engaged in experiential learning activities that troubled commonsense understandings of sexuality, sex and gender. The paper aims to provide educators and administrators with ideas on how a comprehensive queer-inclusive English literature curriculum can be implemented in high schools.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; genre; identités LGBTQIA2+; pédagogie; périodes historiques; queer; régions géographiques; sexualité; thématiques; école secondaire; états-unis

Se retrouver entre soi pour se reconnaitre: conceptions du genre et regulation des echanges dans un forum de personnes trans - Pastinelli, Madeleine; Dery, Caroline (Anthropologie et Societes, 2016)
Les possibilités de communication anonyme permises par les nouvelles technologies amènent des personnes qui ont en commun des pratiques ou des expériences qui les stigmatisent à se retrouver à l’abri des regards pour échanger entre elles et former des communautés en ligne. Ce faisant, elles se réapproprient leur expérience dans un langage choisi qui leur permet de redonner sens à des identités et des pratiques marginales ou considérées comme déviantes ou pensées comme relevant de la pathologie par le discours médical. L’enquête que nous avons menée dans une communauté en ligne de personnes trans éclaire la manière dont la fréquentation de celle-ci permet à ces personnes de se (re)connaître dans leur expérience particulière du corps et du genre et de faire sens de cette expérience. La volonté communément partagée par ces personnes de penser autrement leur expérience donne lieu à la rencontre d’une multitude de conceptions différentes, et parfois incompatibles entre elles, de l’identité de genre et de l’expérience trans. L’analyse se penche plus particulièrement sur la régulation du discours et des échanges qui est faite par les modérateurs dans ce contexte et sur le type de consensus qu’elle rend possible.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; outils; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; transféminisme

True loves, dark nights: Queer performativity and grieving through music in the work of Rufus Wainwright - Salerno, Stephanie (Université d'État de Bowling Green, 2016)
This dissertation studies the cultural significance of Canadian-American singer/songwriter Rufus Wainwright's (b. 1973) album All Days Are Nights: Songs for Lulu (Decca, 2010). Lulu was written, recorded, and toured in the years surrounding the illness and eventual death of his mother, beloved Quebecoise singer/songwriter Kate McGarrigle. The album, performed as a classical song cycle, stands out amongst Wainwright's musical catalogue as a hybrid composition that mixes classical and popular musical forms and styles. More than merely a collection of songs about death, loss, and personal suffering, Lulu is a vehicle that enabled him to grieve through music. I argue that Wainwright's performativity, as well as the music itself, can be understood as queer, or as that which transgresses traditional or expected boundaries. In this sense, Wainwright's artistic identity and musical trajectory resemble a rhizome, extending in multiple directions and continually expanding to create new paths and outcomes. Instances of queerness reveal themselves in the genre hybridity of the Lulu song cycle, the emotional vulnerability of Wainwright's vocal performance, the deconstruction of gender norms in live performance, and the circulation of affect within the performance space. In this study, I examine the song cycle form, Wainwright's musical score and vocal performance, live performance videos, and fan reactions to live performances in order to identify meaningful moments where Wainwright's musical and performative decisions queer audience expectations. While these musical moments contribute to the already rich and varied lineage of the gay male artist in both classical and popular music, I argue that Wainwright's queer performativity and nontraditional musical choices speak to larger issues important to American culture in the contemporary moment. These issues include the visibility of male public mourning and the healing power of artistic expression in the face of traumatic loss.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; culture populaire; deuil; discipline; genre; mémoires/thèses; philosophie; périodes historiques; queer; ressource en ligne; résistance; sciences humaines; émotions